Pengaruh Self Efficacy, On the Job Training dan Fasilitas Kerja Terhadap Kinerja Pegawai Kantor Desa (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
Improving employee performance stands as the paramount management challenge, as the company's success and sustainability hinge on the caliber of its human resources. This study aims to scrutinize the impact of Self-Efficacy, On-The-Job Training, and Work Facilities on Employee Performance at the Tengkudak Village Office. With a sample size of 30, employing the total sampling method, data were collected through questionnaires. Multiple linear regression analysis was utilized to assess the influence of the aforementioned factors.The findings revealed that Self-Efficacy, On-The-Job Training, and Work Facilities significantly and positively affect employee performance at the Tengkudak Village Office, both partially and simultaneously. Drawing from these findings, management is advised to boost employee appreciation, evaluate the salary structure, refine training initiatives, and foster stronger communication channels between management and staff. These efforts aim to enhance overall employee performance and well-being. Future research endeavors should consider broadening the sample size, exploring diverse locations, and incorporating additional variables such as motivation and leadership to gain deeper insights into the factors impacting employee performance.